1991
DOI: 10.1136/jmg.28.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Marfan syndrome with congenital arachnodactyly, flexion contractures, and severe cardiac valve insufficiency.

Abstract: We describe a male neonate with severe arachnodactyly, hypermobility of the fingers, flexion contractures of elbows, wrists, hips, and knees, micrognathia, crumpled ears, rockerbottom feet, loose redundant skin, and ocular abnormalities. Severe cardiac valve insufficiency and aortic dilatation resulted in cardiac failure and death 20 hours after birth. This case represents the severe end of the clinical spectum of Marfan syndrome. As similar patients have been reported, they may represent a separate mutation.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…NMS may be diagnosed in the neonatal period if there is a severe phenotype due to combined deficiency of fibrillin and decorin [Superti-Furga et al, 1992]. This condition manifests with abnormal habitus, heart valve insufficiency, cutis laxa, crumpled ears, joint contractures, muscle hypoplasia, congenital anomalies of the eye, and pulmonary hypoplasia [Buntinx et al, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…NMS may be diagnosed in the neonatal period if there is a severe phenotype due to combined deficiency of fibrillin and decorin [Superti-Furga et al, 1992]. This condition manifests with abnormal habitus, heart valve insufficiency, cutis laxa, crumpled ears, joint contractures, muscle hypoplasia, congenital anomalies of the eye, and pulmonary hypoplasia [Buntinx et al, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…Such infants may also display congenital flexion contractures, crumpled ears, loose redundant skin, and a characteristic 'senile' facial appearance. 45 The mean life span is usually low (approximately 1 year 46 ). The primary cause of death is congestive heart failure associated with mitral and tricuspid regurgitation.…”
Section: Neonatal Marfan Syndrome and Fbn1 Gene Mutationsmentioning
confidence: 99%
“…Family investigation usually reveals that the Marfan patients with the severe neonatal phenotype are sporadic cases: Buntinx et al reported that 37 of 44 cases with neonatal manifestations were sporadic. 45 For a long time it was generally thought that the neonatal phenotype could be explained by mutations in a distinct gene than that involved in the classic 'adolescent-adult' form of the syndrome as the observed symptoms were extremely severe and overlapped with congenital contractural arachnodactyly. Godfrey et al…”
Section: Neonatal Marfan Syndrome and Fbn1 Gene Mutationsmentioning
confidence: 99%
“…In addition to skeletal and ocular abnormalities, infants with NMS also have characteristic facial features and the associated severe cardiac abnormalities commonly lead to death before the age of 3 years [7]. Most cases of NMS are sporadic and believed due to de novo autosomal dominant mutations [2].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal Marfan syndrome (NMS) shares many features with Beals contractural arachnodactyly [2]. In addition to skeletal and ocular abnormalities, infants with NMS also have characteristic facial features and the associated severe cardiac abnormalities commonly lead to death before the age of 3 years [7].…”
Section: Introductionmentioning
confidence: 99%